Distonia focal e a atividade do instrumentista de sopro - GARCIA, Ricardo Rosembergue (2012)
This paper discusses the musician's dystonia and its relationship to performance on wind instruments. The work presents from the literature review on the subject the concept of dystonia, as well as the musician's focal dystonia of its main causes and symptoms related to instrumental practice and lists possible ways of prevention based on the aspects of preparation and holding of musical performance and situations related to the theme. The survey data were obtained through consultation with professional musicians in the city of Goiania. The results revealed several meanings of musical practice and overuse, health problems related to performance anxiety and musical performance and still making music that can overcome the physical and mental limits of the performer. Due to the incidence of psychophysical problems in musicians, undertook a discussion about the possibility of developing disorders in brass and it was concluded that the musical performance can generate states of illness and development of disorders such as focal dystonia of the musician. It was recommended a few precautions to be taken as preventive measures for occupational illness.